ENERGY EXPANSION OF GAZPROM AND ITS REFLECTION IN RUSSIA’S EXTERNAL POLICY - Afonin ,; Krivova,; Martynova,; Meshkov ,; Takigawa , Nikiporets (Revista Inclusiones, 2020)
In this article, the authors analyze in detail the current state, tendencies, and development prospects of the gas market and international natural gas trade and characterize Russia’s place in this market. The bigger role of gas in the global market allows Russia to solidify its positions and contributes to deepening economic cooperation between the Russian Federation and the EU provided that energy policy is well-thought-out and there is a prompt reaction to changing market conditions. As regards interaction among Asia Pacific Region countries, Russia must break onto new markets and master the latest technologies.